The causes of economic growth: Revisiting our ignorance - Sá, Jorge; Luís, Ana Lúcia; Rodrigues, Paulo (Edelweiss Applied Science and Technology, 2025)
The sources of economic growth are a recurrent theme in economic literature. However, the full range of factors behind growth remains elusive. We are still somewhat ignorant about the forces that drive economic growth. A large part of economic growth remains unexplained through the typical analysis based on the productive factors of labor and capital. The original idea behind this research is that it moves away from the traditional analysis of economic growth and examines countries from a business perspective. If, in a company, we tend to look at the various sectors, why not look at the determinants of a country’s growth in the same way? Therefore, we embrace the idea that our ignorance can be reduced if we consider countries as organizations whose performance depends on the level of their business administration areas: marketing, finance, human resources policies, information systems management, and research and development. This research aims to revisit previous works and deepen them. The methodology followed consists of improving the statistical analysis by increasing the variables used with a sample of 33 countries over a five-year period. We conclude that the approach is relevant and can explain more than 90% of the variation in per capita income.